Refractive Error Profile in a Tertiary Centre in Western Nepal - Taludhar, S; Dhakal, S (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Refractive error is one of the causes of avoidable blindness. Myopia, hypermetropia and astigmatism are the common types of refractive error. Not many studies are done to detect pattern of refractive error in Western Nepal. So, the study will determine the prevalence and distribution of refractive errors. MATERIALS AND METHODS: A prospective study of all consecutive patients of age less than 40 years who visited eye department, Gandaki Medical College, between May 2010 and May 2011 was conducted. Visual acuity, naked eye and pin hole examination was done by ophthalmic assistant with cycloplegic refraction when needed. Those who did not turn up for refraction were excluded from the study. RESULTS: A total of 601 patients were seen within the study period. Mean age of male patients was 22.4 years }0.6 (95% CI, 21.2-23.6 years) and mean age of female patients was 24.2 years }0.5 (95% CI, 23.2-25.2 years). Majority of the patients were in age group 11-20 years (39.3%). Myopia was the most common refractive error (43.3%) followed by simple myopic astigmatism (23.8%). Refractive errors were more common in females. CONCLUSIONS: Myopia was the commonest refractive compared to hypermetropia. Refractive error was more common in females than in males. Such studies help to know the picture of refractive errors in community and such reports are helpful in planning programme to prevent avoidable blindness. DOI: http://dx.doi.org/10.3126/ijim.v2i2.8324 Int J Infect Microbiol 2013;2(2):59-63